The Place of John Stuart Mill and of Robert Owen in the History of English Neo-Malthusianism - Himes, Norman E. (Quarterly Journal of Economics, 1928)
Misconceptions prevalent on Mill and Owen. — I. James Mill, Place, and Carlile, 628. — Hayward's letter of 1873 on J. S. Mill, 630 — His charges and insinuations, 631. — Mill's letter of 1868, 633 — II. Place's statement of 1823 on Owen, 633. — How intimate was Owen's connection with Neo-Malthusianism, 636 — Owen's letter of denial in 1827, 639.